Analysis of Motivation, Economic Conditions, Trends and Educational Technology on Interest in Continuing Higher Education as a Marketing Strategy for Private Universities in Karawang Regency - Muhammad Akhdiyatul’aein; Umi Narimawati; M Yani Syafei (SAINTIS Publishing, 2025)
Improving the quality of education is an important foundation in preparing Indonesia to face a competitive and dynamic future, one of which is by increasing the level of higher education. Several factors that influence the desire to continue to higher education are motivation, economic conditions and educational trends and technology. The purpose of this study is to analyze motivation, economic conditions, trends and educational technology on the interest in continuing to higher education as a marketing strategy for private universities in Karawang Regency. The type of research used in this study is a quantitative approach, the design of this study uses an observational type and cross-sectional research. The study uses primary and secondary data, the number of subjects is 107 subjects. The study was conducted during December 2024. Data analysis used the Chi-Square Test and the Logistic Regression Multivariate test. The results of the study showed that motivation, economic conditions, trends and educational technology have a relationship with the interest in continuing to higher education. The results of the multivariate test only showed that the economic conditions and motivation variables were related to the desire to continue to higher education, these two variables can be used as a proposal in making strategies in marketing private universities in Karawang Regency.